A History of Boston in 50 Artifacts - Bagley, Joseph M., 1985- (Book collections on Project MUSE., 2021)
"Bagley, city archaeologist of Boston, uncovers a fascinating hodgepodge of history-from ancient fishing grounds to Jazz Age red-light districts-that will surprise and delight even longtime residents. Each artifact is shown in full color with a description of the item's significance to its site location and Boston's larger history"--